2023
DOI: 10.33759/jrki.v5i1.330
|View full text |Cite
|
Sign up to set email alerts
|

FORMULASI DAN UJI STABILITAS SEDIAAN TONER WAJAH EKSTRAK BUAH PARE (Momordica charantia L) SEBAGAI ANTI JERAWAT DENGAN VARIASI SURFAKTAN

Abstract: Bitter gourd extract (Momordica charantia L) contains secondary metabolites such as flavonoids, alkaloids, and saponins that can be antibacterial against acne-causing bacteria (Propionibacterium acnes). Momordica charantia L., could make into facial toner preparations to prevent the emergence and worsen acne. It is formulated with various concentrations of polysorbate 20 and performs stability testing. This study aimed at the optimal formula and analyzed the variations in the concentration effect of polysorbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The color of the toner preparation obtained is white. The form of the toner preparation produced is liquid so it is easy to apply, (Noor et al, 2023) reported that a toner preparation that has a high viscosity can make the skin feel sticky to the skin, making it uncomfortable when using the toner. The aroma of the toner is the distinctive smell of red betel which is quite strong, it is necessary to add the right fragrance to avoid difficulties with the strong aroma of red betel.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The color of the toner preparation obtained is white. The form of the toner preparation produced is liquid so it is easy to apply, (Noor et al, 2023) reported that a toner preparation that has a high viscosity can make the skin feel sticky to the skin, making it uncomfortable when using the toner. The aroma of the toner is the distinctive smell of red betel which is quite strong, it is necessary to add the right fragrance to avoid difficulties with the strong aroma of red betel.…”
Section: Resultsmentioning
confidence: 99%
“…(2) pH test, The degree of acidity (pH) test was measured using a pH meter. A good pH value for toner preparations is 4.5-6.5 (Noor et al, 2023) (3) Homogeneity Test (4) The homogeneity test is carried out by observing whether there are materials or ingredients used that are not mixed evenly or there are residues that have not dissolved. ( 5) Viscosity Test Testing the viscosity of the toner preparation was carried out using a viscometer with spindle number 1 at a speed of 60 rpm.…”
Section: (C) Physical Quality Test Of Toner Preparationsmentioning
confidence: 99%
See 3 more Smart Citations